Consumers' perspective towards Malaysian traditional food: sambal belacan (chilli shrimp paste), a preliminary investigation. - Abdul Karim, Muhammad Shahrim; Abdul Rashid, Siti Sumayah; Mohd Adzahan, Noranizan; Camillo, Angelo A. (Federal Agricultural Marketing Authority (FAMA), 2011)

(untitled)
Sambal belacan or chilli shrimp paste is a condiment that is widely consumed by Malaysians. With the aim to gather information concerning the elaborated definition of the term “sambal belacan”, four focus group sessions were conducted. Three key themes to convey the definition were presented from the analyses of the transcripts. These were ingredients, techniques and sensory attributes of Malaysian sambal belacan. The results suggest that the basic ingredients for sambal belacan are fresh chillies, belacan and salt. The mixture, when pounded in a mortar with a pestle, produces a desirable texture. There were 38 varieties of additional ingredients reported. Most participants stated that it enhances appetite for enjoying meals. The participants also stated unfavourable characteristics of sambal belacan due to the presence of chilli seeds, watery texture and strong aroma of belacan. Research on product development of sambal belacan is recommended as it is crucial to explore consumers’ demands for new varieties of sambal belacan and market it as one of Malaysia’s food identity.